Thermohydraulic Performance Improvement in Heat Exchanger Square Duct Inserted with 45° Inclined Square Ring. (13th January 2020) - Boonloi, Amnart; Jedsadaratanachai, Withada
Abstract : Thermal performance development, heat transfer structure, and flow behavior in the heat exchanger square duct equipped with a 45° inclined square ring are investigated numerically. The effects of flow blockage ratios and spacing ratios for the inclined square ring on fluid flow and heat transfer are considered. The Reynolds number (Re = 100–2000, laminar regime) based on the hydraulic diameter of the square duct is selected for the present work. The numerical domain of the square duct inserted with the 45° inclined square ring is solved with the finite volume method. The SIMPLE algorithm is picked for the numerical investigation. The heat transfer characteristics and flow topologies in the square duct inserted with the inclined square ring are plotted in the numerical report. The heat transfer rate, pressure loss, and efficiency for the square duct placed with the inclined square ring are presented in forms of Nusselt number, friction factor, and thermal enhancement factor, respectively. As the numerical results, it is detected that the heat transfer rate of the heat exchanger square duct inserted with the inclined square ring is around 1.00–10.05 times over the smooth duct with no inclined square ring. Additionally, the maximum thermal enhancement factor for the heat exchanger square duct inserted with the inclined square ring is around 2.84.